The impact of entrepreneurship education on university students' entrepreneurial intention: a study at UiTM Cawangan Pulau Pinang / Nurfarahin Nabila Fauzi … [et al.] - Fauzi, Nurfarahin Nabila; Mohamad Saber, Joesri; Salim, Azlan; Ibrahim, Mohd Zool Fadli; Bahari, Khairil Anuar (Universiti Teknologi Mara Cawangan Pulau Pinang, 2025)
Entrepreneurship education has been recognised as critical in shaping students' entrepreneurial mindset and career intentions. Despite various initiatives to embed entrepreneurship into higher education curricula, many university graduates still lack the confidence and motivation to venture into entrepreneurship, opting for traditional employment pathways. This lack of confidence and preference for traditional employment raises concerns about the effectiveness of entrepreneurship education in fostering actual entrepreneurial outcomes among students. Thus, this study aims to examine the impact of entrepreneurship education on students' entrepreneurial intention, focusing on key factors such as perceived feasibility, propensity to act, and attitude towards entrepreneurship. 275 students from UiTM Cawangan Pulau Pinang participated in this study. The results indicate a strong positive correlation between entrepreneurship education and students' entrepreneurial intention. Findings show that students who undergo structured entrepreneurship training are 25% more likely to pursue entrepreneurship than those with minimal exposure. Additionally, perceived feasibility and propensity to act emerged as the strongest predictors of entrepreneurial intention, emphasising the role of self-efficacy and confidence in business decisions. However, the sample size and geographical scope of this study limit its generalisability. Future research should explore longitudinal studies to assess the long-term effects of entrepreneurship education on graduates' entrepreneurial success. These findings provide valuable insights for universities and policymakers in designing more effective entrepreneurship programs to nurture future entrepreneurs and contribute to the national economic landscape.